2004
DOI: 10.1023/b:jmsm.0000032820.50983.c1
|View full text |Cite
|
Sign up to set email alerts
|

Implants coated with bioactive glass by CO2-laser, an in vivo study

Abstract: Due to ageing of the population, the number of revision operations is expected to increase. Thus good fixation of medical implants is crucial for successful treatment. In our previous studies, a method to coat titanium implants with bioactive glass (BAG) via CO2 laser treatment was introduced. It allows to localise the application of a bioactive coating, without heat treatment of the whole implant. In the present study, cylindrical titanium implants were used (BAG-coated, control group: NaOH-treated and grit-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
2
28
0
1
Order By: Relevance
“…A great number of materials are used today to replace damaged bones and tissues, including metallic materials due to their excellent mechanical properties, such as strength and hardness. Unfortunately, these materials have two main disadvantages: 1) the tendency to release metallic ions when exposed to body fluids and 2) the formation of a non-adherent fibrous capsule around implant [6][7][8][9][10] . Considering these disadvantages, ceramic materials (bioactive materials) have been successfully used to coat metallic materials for decades.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of materials are used today to replace damaged bones and tissues, including metallic materials due to their excellent mechanical properties, such as strength and hardness. Unfortunately, these materials have two main disadvantages: 1) the tendency to release metallic ions when exposed to body fluids and 2) the formation of a non-adherent fibrous capsule around implant [6][7][8][9][10] . Considering these disadvantages, ceramic materials (bioactive materials) have been successfully used to coat metallic materials for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, osteoconductivity is the ability of an implant surface to conduct the growth of the bone over its surface. Similar studies con rm the reliability of implant surface laser treatment techniques [6,[17][18][19]. Many studies stressed how laser treatment on smooth titanium implant surfaces induced a unique morphology, without cavitylike features or other morphological elements that could contain irremovable contaminations, such as traces of aluminium or silica le over from implant sandblasting [2,20].…”
Section: Discussionmentioning
confidence: 72%
“…Even if animals are not ideal models for humans because of the intrinsic metabolic, anatomic and cellular differences that can give inadequate or erroneous information 67) , similar data had been allegedly reported in animal models by Moritz et al 59) and by Wheeler et al 68) who found that, in presence of B-G coating, implants were integrated into host bone without a connective tissue capsule and were surrounded by significantly more bone tissue than the control implants.…”
Section: Metal Surface Biofunctionalization: Coating Materials For Denmentioning
confidence: 64%
“…It has been established that the rate of surface reaction of B-G to body tissues is very fast (within hours) in comparison to SHA 25) and that calcium sodium phosphosilicates can develop a chemical bond with living bone that is stronger than either the bone or ceramic alone 2) . Because of its high IB, B-G is regarded as a viable alternative to cover metallic implants in order to combine the best properties of both materials 59) . On this account, the B-G coating may improve the rate of commitment of bone precursor cells to osteoblastic lineage differentiation and the resultant implants display a more rapid interfacial bone formation, with consequent stabilization at an early stage, load bearing capacity in poor quality bone along with whole treatment time reduction.…”
Section: Metal Surface Biofunctionalization: Coating Materials For Denmentioning
confidence: 99%
See 1 more Smart Citation